Planning of Library Automation in Kannada University Hampi (karnataka): a Study - Lohar, M. S.; Naik, M. Nagaraj (Journal of Information and Knowledge, 2013)
This paper throws light on the step-by-step process of library automation in Kannada University, Hampi. Kannada University specialized in Kannada studies and have specialized research centers. This study attempts to understand the need for the library automation, requirements of hard ware, and Benefits of SOUL is given.